218 PERSISTENT LEFT SUPERIOR VENA CAVA IN AN ADULT PATIENT WITH AN IMPLANTED PACEMAKER: A CASE REPORT. (15th December 2022) - Varriale, Alessandro; Nannelli, Chiara; Springhetti, Paolo; Rossi, Andrea; Bergamini, Corinna; Tafciu, Elvin; Maffeis, Caterina; Ribichini, Flavio Luciano; Benfari, Giovanni
Abstract: Introduction: Persistent left superior vena cava (PLSVC) is the most common thoracic venous anomaly, although infrequent in the general population (prevalence estimates as 0.2-3%). It begins at the junction of the left subclavian and internal jugular veins, passes through the left side of the mediastinum adjacent to the aortic arch, and mostly drains into the right atrium via the coronary sinus (CS). For the majority of cases it is asymptomatic and it is mostly detected incidentally. More rarely it can be associated with other congenital abnormalities, such as aortic bicuspid valve, aortic coartation or atrial septal defects. Besides, in less than 10% of the cases the left superior vena cava drains in the left atrium, leading to a right-to-left shunt. Lastly, it can lead to arrhythmic problems. Case presentation: A 85-year-old man was admitted to the emergency department for syncope. Previous medical history was unknown and there was no clinical documentation available. The electrocardiogram showed an atrial fibrillation and some pacemaker-induced beats. An echocardiogram was performed, which showed dilation and dysfunction of the right chambers and a dilated CS. Moreover, the same exam revealed the two pacemaker leads passing through the CS and ending their course into the right atrium and ventricle. The chest X-ray displayed the pacemaker leads passing to the left side of the aorta. Furthermore, a computed tomography angiography was performed in the suspicion of a pulmonary embolism. The exam showed small vascular filling defects in arteries of the right inferior lung lobe, but also the presence of two superior vena cavas, with the left one draining into the CS. The pacemaker leads passed from the left subclavian vein through the left superior vena cava reaching the right chambers. Therefore, the diagnosis of PLSVC was confirmed. Discussion and Conclusions: Despite the benign natural history of this diagnosis, it is important to know the existence of this condition. PLSVC can be suspected when a dilated CS is detected on a transthoracic echocardiogram, with a parasternal long axis view. The best projections to visualize the dilatation of CS are also the apical four-chamber and the subcostal view. Besides, the direct detection of left superior vena cava can be obtained with a suprasternal view. The presence of the right superior vena cava should also be confirmed with a subcostal or suprasternal view. The differential diagnosis for a dilatation of the CS includes anomalous pulmonary venous return with a pulmonary vein draining in the CS, the "unroofed coronary sinus", a tricuspid regurgitation with a jet directed towards the CS, elevated right-chamber filling pressures. The diagnosis of PLSVC can be confirmed with a saline contrast echocardiography ("bubble-test") or with other radiological investigations (computed tomography or magnetic resonance). It should be reported in radiological reports even when it is an incidental finding because of its clinical relevance: it is essential to know its presence in advance in invasive procedures, such as pacemaker implantation, ablative procedures, cardiac surgery, because it could affect the proper approaches and could lead to complications. Moreover, in a minority of cases, it can be associated with other congenital abnormalities or with arrhythmic problems.